(untitled) (Eurasian Research Bulletin, 2022)
This article discusses the 2 most modern technologies used in geodesy and cartography today. It has South N3 andi73+IMU(GNSS) modern technology working processes and mutual advantages are explained with the help of research studies. According to him time taken to complete work on the South N3 electronic tachymeter apparatus i73+IMU(GNSS) was found to be much longer than the execution time on the GPS device.